Горе от ума: [сборник] / А. С. Грибоедов - Грибоедов Александр Сергеевич (Эксклюзив: Русская классика, 2018)
Экземпляры: ф.8 (20190118) / Инвентарный номер: 59174 / Цена: / Сис.шифр: 84(2Рос=Рус)1-6 / Авт.знак: Г 82 / ГРНТИ: 17.82.20 / ББК: 84(2Рос=Рус)1-6